2016
DOI: 10.1002/smll.201503722
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Emerges as a Versatile Template for Materials Preparation

Abstract: Graphene and its derivatives are emerging as a class of novel but versatile templates for the controlled preparation and functionalization of materials. In this paper a conceptual review on graphene-based templates is given, highlighting their versatile roles in materials preparation. Graphene is capable of acting as a low-dimensional hard template, where its two-dimensional morphology directs the formation of novel nanostructures. Graphene oxide and other functionalized graphenes are amphiphilic and may be se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 115 publications
(161 reference statements)
0
33
0
Order By: Relevance
“…[1][2][3][4][5][6][7] Toward macro applications, graphene oxide (GO), [8][9][10][11][12][13][14][15] a well-known solution processable precursor of graphene, has been mostly studied as a universal starting material, which overcomes the processing difficulties of graphene due to its intrinsic insolubility. The GO, which is generally obtained by solution oxidation of graphite with strong oxidizing reagents (e.g., potassium permanganate (KMnO 4 ) and concentrated sulfuric acid (H 2 SO 4 ) in a modified Hummers method) and can be further transformed into reduced graphene oxide (RGO) upon diverse reduction strategies, [16][17][18] features excellent solution processing capability as well as massive manageability and manipulation properties, thanks to the presence of a large number of epoxy and hydroxyl groups on its basal plane and carboxyl groups (-COOH)) on the peripheral interface.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7] Toward macro applications, graphene oxide (GO), [8][9][10][11][12][13][14][15] a well-known solution processable precursor of graphene, has been mostly studied as a universal starting material, which overcomes the processing difficulties of graphene due to its intrinsic insolubility. The GO, which is generally obtained by solution oxidation of graphite with strong oxidizing reagents (e.g., potassium permanganate (KMnO 4 ) and concentrated sulfuric acid (H 2 SO 4 ) in a modified Hummers method) and can be further transformed into reduced graphene oxide (RGO) upon diverse reduction strategies, [16][17][18] features excellent solution processing capability as well as massive manageability and manipulation properties, thanks to the presence of a large number of epoxy and hydroxyl groups on its basal plane and carboxyl groups (-COOH)) on the peripheral interface.…”
mentioning
confidence: 99%
“…19,20 As a plus, the specific functional groups (e.g., -COOH) on the GO can be further applied as versatile anchoring points to direct the assembly of diverse species with matching functional groups (e.g., inorganic nanoparticles and polymers containing amino groups that can react with -COOH groups to form amides) on the GO, toward the construction of functional hybrid materials for diverse applications. 8 With these merits, the glamorous role of GO has been widely demonstrated in different areas, representing a popular and facile way to utilize graphene materials on a large scale. Unfortunately, the GO, and also its reduced counterparts or derivatives, often bear numerous irremediable structural defects or large holes on the basal plane, which severely degrade the mechanical, thermal and electrical properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Their superior electrical conductivity increases electron transfer in the formed structure and the conductivity of the whole electrode; (2) the large surface area of graphene sheets offers more anchoring sites for other non-carbon active materials, such as metal and metal oxide nanoparticles and conductive polymers, enabling both their high activity and utilization; (3) the mechanical properties and flexibility of graphene buffer any volume expansion during the electrochemical reactions and guarantee the integrity of the electrochemical reaction framework; (4) the surface functional groups on graphene help confine the growth of non-carbon active material and build a bridge between the graphene and the active material to enhance reaction activity [18]; (5) the flexibility of graphene and its derivatives makes them promising versatile templates for energy storage material synthesis [19,20]. These advantages are transferred from graphene to graphene-derived carbons by controlling the assembly process.…”
Section: Individual Sheetsmentioning
confidence: 99%
“…Recently, it has been demonstrated that graphene may serve as a template for epitaxial growth of organic and inorganic materials . Owing to its hybridized sp 2 bonding of carbon atoms in a hexagonal pattern over a large sheet, graphene can be an ideal template for crystal growth.…”
mentioning
confidence: 99%